Supremasi Hukum Pidana di Indonesia - Sholihin, Bunyana (Unisia, 2012)
Supremacy of law has been an ideal for the Rechsstaat, such as Indonesia, in the sense that law is enforced and effective over every thing. Based on sociology of law theory, law could be enforced and effective in a national community if it conformed the legal spirit of the relevant nation. Ideally, therefore, for the supremacy of law, the criminal laws of Indonesia are those in conformity with the spirit of truth and justice trusted and embraced by Indonesian nation, because such laws are the only ones reflecting the spirit of Indonesian nation. Keywords: supremacy of law, Indonesia, criminal law, spirit